2021
DOI: 10.1016/j.ebiom.2021.103444
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic miRNA signature for pulmonary arterial hypertension using a consensus machine learning approach

Abstract: Background: Pulmonary arterial hypertension (PAH) is a rare but life shortening disease, the diagnosis of which is often delayed, and requires an invasive right heart catheterisation. Identifying diagnostic biomarkers may improve screening to identify patients at risk of PAH earlier and provide new insights into disease pathogenesis. MicroRNAs are small, non-coding molecules of RNA, previously shown to be dysregulated in PAH, and contribute to the disease process in animal models. Methods: Plasma from 64 treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 46 publications
(44 reference statements)
0
30
0
Order By: Relevance
“…miR-214 antagonists have been reported to alleviate the phenotypic changes and proliferation of smooth muscle cells in vascular hyperproliferative diseases, including PAH [ 7 ]. In a consensus machine learning approach study, it was found that miR-636 and miR-187-5p could predict PAH diagnosis with high accuracy [ 8 ]. These studies suggest that miRNAs may be new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…miR-214 antagonists have been reported to alleviate the phenotypic changes and proliferation of smooth muscle cells in vascular hyperproliferative diseases, including PAH [ 7 ]. In a consensus machine learning approach study, it was found that miR-636 and miR-187-5p could predict PAH diagnosis with high accuracy [ 8 ]. These studies suggest that miRNAs may be new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Supervised ML has also been exploited to detect circulating molecular signatures of PAH. For example, Errington et al 51 Finally, researchers used supervised ML to preemptively sniff out PAH from electronic health record data. 32 Training a gradient boosted decision trees algorithm on patient-level resource utilization data, a model capable of classifying individuals most likely to later develop idiopathic PAH was developed.…”
Section: Supervised Learning In Phmentioning
confidence: 99%
“…Supervised ML has also been exploited to detect circulating molecular signatures of PAH. For example, Errington et al 51 used an ensemble ML strategy (consensus predictions across random forest, regression partition trees, least absolute shrinkage and selection operator regression, and boosted decision trees algorithms) to uncover a microRNA signature of PAH. Network-based pathway analyses identified the corresponding miRNA gene targets, which accurately discriminated PAH cases in public transcriptomic data sets.…”
Section: How To Harness Big Data Sets In Ph?mentioning
confidence: 99%
“…In addition, studies have looked at the correlation between the expression profiles of dysregulated miRNAs and the disease severity or survival rate of pulmonary arterial hypertension (PAH) patients. Multiple promising miRNAs have been considered as biomarker of PAH disease that are being actively evaluated [ 16 , 17 ]. Aside from miRNAs, lncRNAs and circRNAs are other two major groups of ncRNAs relatively less investigated and understood in the PH field.…”
Section: The Noncoding Rna Transcriptome In Pulmonary Hypertensionmentioning
confidence: 99%